Reinventing government : how the entrepreneurial spirit is transforming the public sector - Osborne, David (New York : Penguin Books USA Inc., 1993)
This American study looks at how the entrepreneurial spirit is transforming the public sector.
1. Catalytic government - steering rather than rowing -- 2. Community-owned government - empowering rather than serving -- 3. Competitive government - injecting competition into service delivery -- 4. Mission-driven government - transforming rule-driven organizations -- 5. Results-oriented government - funding outcomes, not inputs -- 6. Customer-driven government - meeting the needs of the customer, not the bureaucracy -- 7. Enterprising government - earning rather than spending -- 8. Anticipatory government - prevention rather than cure -- 9. Decentralized government - from hierarchy to participation and teamwork -- 10. Market-oriented government - leveraging change through the market -- 11. Putting it all together.
Includes bibliographical references and index.
Keywords: POLITICS AND GOVERNMENT